Keterlibatan Masyarakat Dalam Pembentukan Undang-Undang Sebagai Bentuk Impementasi Demokrasi - Itok Dwi Kurniawan; Pipit Widiatmaka; Samuel Bintang Robby (Universitas Pendidikan Nasional, 2023)
This article examines the relationship between community participation in the formation of laws and the democratic system, the role of society in the process of forming laws, and community constraints in participating in the process of forming laws. The results of the study in this article show that community involvement in shaping laws is the main key to a country that adheres to democracy, so it is closely related to community involvement in the formation of laws and democracy. The process of forming a law goes through several stages, namely planning, drafting, discussing ratification, and promulgation. Good laws must uphold the principles of legal certainty and justice and aim to advance the welfare of the community. Community involvement in forming laws is very important, considering that the law if it has been passed and promulgated will have direct implications for the community. State institutions that hold legislative functions in the formation of laws must involve the community.